2022
DOI: 10.3390/jfb13040257
|View full text |Cite|
|
Sign up to set email alerts
|

Sinus Mucosal Damage Triggered by Synthetic or Xenogeneic Bone Substitutes: A Histological Analysis in Rabbits

Abstract: Background: It has been shown in rabbit models that the sinus mucosa in contact with graft particles might experience a progressive thinning and perforations. The phenomenon depends on the graft used. Hence, the aim of the present study was to compare the damaging effects of a synthetic of a xenogeneic graft. Methods: Forty New Zealand rabbits received a bilateral sinus elevation. Both sinuses of twenty rabbits were grafted with a biphasic 60% hydroxyapatite and 40% β-tricalcium phosphate while the other twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…It has been shown that damage occurs in the mucosa in contact with granules of biomaterial [17][18][19][20] or even with implant apexes and threads [18,21]. It has also been shown that grafts with a lower resorption rate present more damage than those with a higher resorption rate [17][18][19][20]. The results of these experiments suggest that resorption and surface characteristics might play an important role in the possible damage to the SM.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…It has been shown that damage occurs in the mucosa in contact with granules of biomaterial [17][18][19][20] or even with implant apexes and threads [18,21]. It has also been shown that grafts with a lower resorption rate present more damage than those with a higher resorption rate [17][18][19][20]. The results of these experiments suggest that resorption and surface characteristics might play an important role in the possible damage to the SM.…”
Section: Introductionmentioning
confidence: 83%
“…This damage, represented by thinning of the SM and perforations, has been observed in a rabbit model. It has been shown that damage occurs in the mucosa in contact with granules of biomaterial [17][18][19][20] or even with implant apexes and threads [18,21]. It has also been shown that grafts with a lower resorption rate present more damage than those with a higher resorption rate [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This outcome of the complete absence of perforations is not in agreement with the reported outcomes of similar studies. In these studies, it was shown that sharpened edges of the granules [32][33][34][35] and implant apexes and threads [33,36] in contact with sinus mucosae produced thinning and possibly perforations over time. These differences are due to the different analytical methods applied.…”
Section: Discussionmentioning
confidence: 99%
“…In the original publication [1], there was a mistake in the legend for Figure 1. The legend of Figure 1a was wrong because it did not describe the correct figure that should have been used.…”
Section: Figure Legendmentioning
confidence: 99%